Long-term effects of elemental composition of particulate matter on inflammatory blood markers in European cohorts. (September 2015) - Hampel, Regina; Peters, Annette; Beelen, Rob; Brunekreef, Bert; Cyrys, Josef; de Faire, Ulf; de Hoogh, Kees; Fuks, Kateryna; Hoffmann, Barbara; Hüls, Anke; Imboden, Medea; Jedynska, Aleksandra; et al.
Abstract: Background: Epidemiological studies have associated long-term exposure to ambient particulate matter with increased mortality from cardiovascular and respiratory disorders. Systemic inflammation is a plausible biological mechanism behind this association. However, it is unclear how the chemical composition of PM affects inflammatory responses. Objectives: To investigate the association between long-term exposure to elemental components of PM and the inflammatory blood markers high-sensitivity C-reactive protein (hsCRP) and fibrinogen as part of the European ESCAPE and TRANSPHORM multi-center projects. Methods: In total, 21, 558 hsCRP measurements and 17, 428 fibrinogen measurements from cross-sections of five and four cohort studies were available, respectively. Residential long-term concentrations of particulate matter < 10 μm (PM10 ) and < 2.5 μm (PM2.5 ) in diameter and selected elemental components (copper, iron, potassium, nickel, sulfur, silicon, vanadium, zinc) were estimated based on land-use regression models. Associations between components and inflammatory markers were estimated using linear regression models for each cohort separately. Cohort-specific results were combined using random effects meta-analysis. As a sensitivity analysis the models were additionally adjusted for PM mass. Results: A 5 ng/m 3 increase in PM2.5 copper and a 500 ng/m 3 increase in PM10 iron were associated with a 6.3% [0.7; 12.3%] and 3.6% [0.3; 7.1%] increase in hsCRP, respectively. These associations between components and fibrinogen were slightly weaker. A 10 ng/m 3 increase in PM2.5 zinc was associated with a 1.2% [0.1; 2.4%] increase in fibrinogen; confidence intervals widened when additionally adjusting for PM2.5 . Conclusions: Long-term exposure to transition metals within ambient particulate matter, originating from traffic and industry, may be related to chronic systemic inflammation providing a link to long-term health effects of particulate matter.